Diversidade genética de Euphractus sexcinctus (Linnaeus, 1758) em áreas de Cerrado e Pantanal - Fischer, Eliana Michelle Paviotti (2016)
Euphractus sexcinctus is a species of armadillo endemic to the South American continent, that has wide distribution and occurs in all Brazilian biomes. Although generalist, with some tolerance to environmental changes, the species is very threatened by anthropogenic pressures, mainly by roadkill. Therefore, this study aimed to provide genetic information for the species, increasing the understanding of the distribution of genetic diversity and its population genetic structure. To access the genetic diversity of the species, its complete genome was sequenced by next generation sequencing. From the sequencing data, the complete mitochondrial genome was assembled. The mitogenoma was considered as subspecies level: Euphractus sexcinctus flavimanus. Besides mitogenoma nuclear microsatellites markers were developed. These microsatellites were used to evaluate the distribution of genetic diversity of the species in areas of Cerrado and Pantanal. Molecular markers were used to identify the sex of the animals, since this identification was not performed during collection. The possibility of molecular sexing in armadillos can be useful, especially when studying carcasses. The data for mitochondrial genome of E. s. flavimanus showed differences, mainly in the control region (D-loop) in comparison to the mitochondrial genome of E. sexcinctus recently sequenced. Regarding the genetic diversity rates, high values were observed for the species in all sampled areas, which is expected to not endangered species. The Bayesian analysis and the molecular variance (AMOVA) analysis exposed a panmitic population of E. sexcinctus in part of the Mato Grosso do Sul, including areas of Cerrado and Pantanal. This fact should not discourage, however, conservation measures for the species, as thought he factorial correspondence analysis (FCA) showed that individuals in some areas barely overlap. In addition, the FST calculations indicated a significant, but very low, structuraction between individuals of cerrado and Pantanal. Molecular sexing showed males are more run dwon than females in two large sampled portions of the BR262. Data on roadkill showed several hotsposts roadkill. This data is useful for taking mitigating measures. However, more detailed data about the surrounding landscape become necessary to better understand the distribution of roadkill on highways sampled and ecology of this species of armadillo.